Subacute Urinary Retention due to a Subpubic Cartilaginous Cyst Treated with Surgical Resection and Internal Fixation: A Case Report and Review of the Literature - Yu Taniguchi; Hiroshi Kamada; Hisashi Sugaya; Tomofumi Nishino; Hajime Mishima; Naoyuki Ochiai; Masashi Yamazaki (Case Reports in Orthopedics)
A subpubic cartilaginous cyst is a rare mass lesion derived from the pubic symphysis, which can cause acute or subacute urinary retention. We report a case of a subpubic cartilaginous cyst in a 62-year-old woman that caused lower abdominal pain and subacute urinary retention, requiring surgical resection. On physical examination, a hard, flexible, nontender mass, 4 cm in diameter, was palpable along the lower border of the pubic bone, extending to the perineum. Magnetic resonance imaging revealed a clearly distinct (3.8 cm × 3.8 cm × 7.2 cm) mass on the midpelvic side of the pelvis, centered on the pubic joint. We proceeded with en bloc resection of the mass, including a resection margin of 1 cm on either side. The bony defect was fixed with a locking plate. On pathological assessment, the mass was diagnosed as a subpubic cartilaginous cyst arising from the cartilage of the pubic symphysis. No tumor recurrence was identified over a 4-year follow-up. Based on our experience, we propose that en bloc resection of the mass, including a wider resection centered on the pubic symphysis, with internal fixation, is a possible treatment for a subpubic cartilaginous cystic mass lesion.